Quality of school life in Turkey, Finland and South Korea - Ayşe Elitok Kesici; Veysel Karani Ceylan (International Journal of Evaluation and Research in Education (IJERE), 2020)
This study was aimed to compare the major studies conducted on the quality of school life in Turkey, Finland and South Korea. The study focuses on which dimensions of quality of school life research in these three countries were examined, their participants, school levels and research methods. This research is in the literature review model. In this context, data were obtained by scanning the related books, theses and articles. In the research, document analysis technique of qualitative research method was used to collect data. Based on the research findings, it is seen that research studies have been conducted in Finland to establish the theoretical framework for conceptualization of the subject. Qualitative, quantitative and mixed methods were used in research studies conducted in South Korea. In the research conducted in three countries, the concept of self, bullying, implicit program, gender, socio-economic level, classmate, teacher and family support, self-efficacy, music, living environment, self and teacher-learner relationship have been determined to affect quality of school life. In the research studies conducted in Turkey, levels of quality of school life were detected, whereas in the research studies conducted in South Korea, the importance of traditional values of Confucius doctrine were focused on.